Class Divisions in Serial Television - Lemke, Sieglinde; Schniedermann, Wibke; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book brings the emergent interest in social class and inequality to the field of television studies. It reveals how the new visibility of class matters in serial television functions aesthetically and examines the cultural class politics articulated in these programmes. This ground-breaking volume argues that reality and quality TV's intricate politics of class entices viewers not only to grapple with previously invisible socio-economic realities but also to reconsider their class alignment. The stereotypical ways of framing class are now supplemented by those dedicated to exposing the economic and socio-psychological burdens of the (lower) middle class. The case studies in this book demonstrate how sophisticated narrative techniques coincide with equally complex ways of exposing class divisions in contemporary American life and how the examined shows disrupt the hegemonic order of class. The volume therefore also invites a rethinking of conventional models of social stratification. .
Introduction: Class Di_visions and the Cultural Politics of Serial Television.Sieglinde Lemke and Wibke Schniedermann -- Part I.(Di)Vision: "Lower" Class Televisibility -- 1.Framing Class, Vicarious Living, and Conspicuous Consumption.Diana Kendall -- 2.American Media's Class Distinctions: "Hillbillies," "Welfare Queens," and "Teen Moms".Diana Owen -- 3.The Paradoxical Class Politics in Here Comes Honey Boo Boo.Evangelia Kindinger -- 4.Reality TV and Its Audiences Reconsidered: Class and Poverty in Undercover Boss.Tanja Aho. Part II.Di*Visions: Screening Exploitation, Neoliberal Lies, and the Politics of Class Realignment -- 5.Lifestyle Precarity and Creative Class Affirmation in Girls.Eric C. Erbacher -- 6.House of Lies and the Management of Emotions.Stefanie Mueller -- 7.The Financialization of Domestic Space in Arrested Development and Breaking Bad.Julia Leyda -- 8.Realignment and Televisual Intellect: The Telepraxis of Class Alliances in Contemporary Subscription Television Drama.Stephen Shapiro .
Keywords: Motion pictures and television; Screen Studies; Film Theory